PENGARUH PEMBERIAN PUPUK BOKASHI FESES AYAM DAN DAUN KIRINYUH DENGAN LEVEL YANG BERBEDA (0; 7,5; 15; DAN 22,5 TON/HA) TERHADAP TINGGI TANAMAN DAN PRODUKSI BERAT KERING TANAMAN RUMPUT ODOT PERTUMBUHAN KE TIGA - Ramu, Meriyana Ata; Sudarma, I Made Adi (Universitas Veteran Bangun Nusantara, 2024)
This research aims to see the re-production of odot grass (Pennisetum purpureum Cv. Mott) in the third growth given chicken feces bokashi fertilizer at level 0; 7.5; 15; and 22.5 tonnes/ha. This research was carried out in Kuta Village, Kanatang District, East Sumba Regency for 2 months from June to August 2023. The main materials in this research were odot grass cuttings, chicken feces and kirinyuh (Chromolaena odorata) leaves. The research design used was a completely randomized design (CRD) with 4 treatments and 4 replications where in 1 bed plot there were 9 odot grass cuttings, so that 144 experimental units were obtained. Dry weight analysis was carried out at the MIPA Terpadu Laboratory at Wira Wacana Christian University, Sumba. The results of this research show that the plant height variable with a level of 7.5 tons/ha has a significant effect (P<0.05) with an average yield of 81.50 cm while the dry weight production of odot grass with a level of 7.5 tons/ha gives average yield 126.80 grams/clump. So it can be concluded that by administering chicken feces bokashi fertilizer at a dose of 7.5 tons/ha, it is able to meet the needs for plant height growth and dry weight production of odot grass. Keywords: Bokashi fertilizer, Chicken feces, Chromolaena odorata, Odot grass.